THE REPRESENTATION OF MULTIPLE INTELLIGENCES ON ENGLISH TEXTBOOKS IN INDONESIA - Ani Fitriyani; Nadiah Ma’mun (The Journal Of English Teaching For Young And Adult Learners, 2022)
Textbook has significant roles in the teaching-learning process. A lot of teaching-learning processes throughout the world are conducted with extensive textbooks usage. It occurs because textbooks hold several roles for teaching-learning activity. On the other hand, a theory named Multiple Intelligence Theory (MI Theory) considers that human is born with a fixed amount of intelligence. By applying MI Theory to the English language teaching, the teaching-learning process is expected to accommodate and stimulate students’ intelligence types well, so the students learning output will increase. The objective of the research was to figure out the representation of Multiple Intelligences in the Junior High School English textbooks in Indonesia published by the Ministry of Education and Culture. This research was a content analysis since it was aimed to investigate Multiple Intelligences implementation in the activities of the textbooks. The instrument of this research was a checklist devised by the researchers based on the theoretical and conceptual framework of MI Theory as well as other checklists had made by previous researchers. A careful analysis of the activities resulted that the textbooks mostly catering to verbal/linguistic, interpersonal, musical, and visual/spatial intelligence. The least dominant intelligences were bodily/kinaesthetic, logical/mathematical, intrapersonal, and naturalist intelligence.